A new probable stem lineage crustacean with three-dimensionally preserved soft parts from the Herefordshire (Silurian) Lagerstatte, UK. - Siveter, D; Sutton, MD; Briggs, D; Siveter, D (2007)
A new arthropod with three-dimensionally preserved soft parts, Tanazios dokeron, is described from the Wenlock Series (Silurian) of Herefordshire, England, UK. Serial grinding, digital photographic and computer rendering techniques yielded 'virtual fossils' in the round for study. The body tagmata of T. dokeron comprise a head shield and a long trunk. The head shield bears six pairs of horn-like spines and the head bears five pairs of appendages. The antennule, antenna and mandible are all uniramous, and the mandible includes a gnathobasic coxa. Appendages four and five are biramous and similar to those of the trunk: each comprises a limb base with an endite, an enditic membrane, and two epipodites, plus an endopod and exopod. The hypostome bears a large cone-like projection centrally, and there may be a short labrum. The trunk has some 64 segments and at least 60 appendage pairs. A very small telson has the anus sited ventrally in its posterior part and also bears a caudal furca. Comparative morphological and cladistic analyses of T. dokeron indicate a crustacean affinity, with a probable position in the eucrustacean stem group. As such the epipodites in T. dokeron are the first recorded in a eucrustacean stem taxon. The new species is interpreted as a benthic or nektobenthic scavenger.